Three-Dimensional Quantitative Flow Visualization Around a Thrust Reverser - Hysa, I.; Tuinstra, M.; Sciacchitano, A.; Scarano, F.; Schwartz, N.; Harrison, C.; Gebbink, R. (AIAA, 2023)
Volumetric particle tracking velocimetry measurements are performed in a low-speed wind tunnel to study the flowaround a 1:12-scale aircraft model with jet engines operating with thrust reversers. The engine jet and freestream flowvelocity are varied to yield a jet to freestream velocity ratio of Vjet∕V∞ ranging from 1.5 to 6. Measurements at suchscale (0.5 m3) require the use of strongly scattering helium-filled soap bubbles as flow tracers, which are introduced inboth the jet and the freestream flow. The tracer’s three-dimensional motion is determined using an array of camerasand a Lagrangian particle tracking algorithm. The mean velocity field reveals the jet inner structure as well as itsinteraction with the freestream, the ground board, the nacelle, the fuselage, and the horizontal and vertical tails. Theexperiments allow detection of exhaust reingestion as well as the aerodynamic interference with control surfaces at thetail segments in a single measurement volume. The results are in good agreement with conventional temperature rakemeasurements while adding details of the flow topology and of the large-scale unsteady flow fluctuations. Finally, thejet reversal characteristics with varying freestreams and nozzle pressure ratios are assessed, demonstrating thefeasibility and versatility of volumetric velocimetry measurements for industrial aerodynamics.